Ø¥Ø³ØªØ±Ø§ØªØ¬ÙŠØ§Øª ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆØªØ¹Ù„Ù…Ù‡Ø§ - Aufia Aisa (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2016)
The strategy is a planning to establish how to achieve a determined goal. And refers to experiences and ideas, expectations and objectives, experience and memory, which includes a plan to deliver results from action to achieve these goals. The strategy Teaching and learning refers to the distribution of art, and using instructional media in order to achieve certain goals